Endoplasmic reticulum–mitochondria interplay in chronic pain: The calcium connection. (August 2020) - Yousuf, Muhammad Saad; Maguire, Aislinn D; Simmen, Thomas; Kerr, Bradley J
Chronic pain is a debilitating condition that affects roughly a third to a half of the world's population. Despite its substantial effect on society, treatment for chronic pain is modest, at best, notwithstanding its side effects. Hence, novel therapeutics are direly needed. Emerging evidence suggests that calcium plays an integral role in mediating neuronal plasticity that underlies sensitization observed in chronic pain states. The endoplasmic reticulum and the mitochondria are the largest calcium repositories in a cell. Here, we review how stressors, like accumulation of misfolded proteins and oxidative stress, influence endoplasmic reticulum and mitochondria function and contribute to chronic pain. We further examine the shuttling of calcium across the mitochondrial-associated membrane as a mechanism of cross-talk between the endoplasmic reticulum and the mitochondria. In addition, we discuss how endoplasmic reticulum stress, mitochondrial impairment, and calcium dyshomeostasis are implicated in various models of neuropathic pain. We propose a novel framework of endoplasmic reticulum–mitochondria signaling in mediating pain hypersensitivity. These observations require further investigation in order to develop novel therapies for chronic pain.